AtMMS21: Connecting DNA Repair and Root Development. (February 2018) - Lai, Jianbin; Han, Danlu; Yang, Chengwei
Abstract : Two recent reports show that SUMO ligase AtMMS21 controls the cell cycle through dissociating the E2Fa/DPa complex, and regulates chromatin remodeling by maintaining the stability of BRAHMA. We discuss these novel functions of AtMMS21 and its potential role in linking DNA repair and root development.